Internet and distributed computing systems : 12th International Conference, IDCS 2019, Naples, Italy, October 10-12, 2019, Proceedings /: 12th International Conference, IDCS 2019, Naples, Italy, October 10-12, 2019, Proceedings. (2019) - Unknown
No abstract available